Whose Evidence Counts? Exploring evidence pathways during the Covid-19 crisis in Panama’s Housing Ministry - García de Paredes, Pablo (Anuario de Estudios Centroamericanos, 2022)
This paper explores how is evidence gathered, transformed, and selected during the current COVID-19 crisis, employing Panama’s housing ministry as a case study. We wish to better understand evidence pathways and provide strategies increasing scientific evidence uptake. Our research strategy was organized into a three-step sequential model: 1. The evidence gathering phase: we studied Covid-19’s effects on households deploying 135 surveys (n=135). 2. The evidence transformation phase: studying housing sector evidence assembled by different ministry divisions via 12 surveys and interviews with ministry personnel (n=12), and 3. The evidence selection phase: studying evidence employed by decision-makers, through a semi-structured interview with the housing minister (n=1). Results show that evidence pathways depend on social phenomena, including internal and external political power negotiations, social class identities, and representations of the role of government.